THE RELIGIOUS SEMINARY AND ITS ROLE IN SUPPORTING NATIONAL PRODUCTS FROM THE CUSTOMERS' POINT OF VIEW A SURVEY STUDY OF THE OPINIONS OF A SAMPLE OF PROFESSORS AND STUDENTS OF THE UNIVERSITY OF KUFA - Najihah Mahmmed Taher (American Journal Of Social Sciences And Humanity Research, 2024)
This research, of significant importance, aims to understand the role of the religious seminary in Najaf and its adequacy in supporting national products through seminary directives and guidelines to support and acquire these products and prefer them over foreign products from the perspective of professors and students/University of Kufa. It also seeks to identify the extent of customer preference for these products, a crucial aspect that your participation will greatly contribute to. Since previous years, specifically after the year (2003), there has been a great interest in improving the image of national products and identifying the factors influencing customer attitudes towards them. The research relied on the questionnaire to survey the opinions of a sample of customers represented by professors and students of the University of Kufa, with a total of (75) customers. The questionnaire consisted of (8) questions and used statistical and analytical methods. The research problem arises from a question that is: (What is the role of the religious seminary in supporting national products from the customers' point of view? The importance of the research is evident from the necessity of having such studies to introduce society to the effective and important role of the religious seminary in Najaf Al-Ashraf in supporting products that are produced locally within the borders of Iraq. Your participation in this research will help us to meet the needs of customers for those products, to reduce dealing with foreign products, and to achieve clear tangible results for the role of the religious seminary in supporting Iraqi economic activity as a whole, a role that has been significant throughout history.